A CoFeCuMn LDH nanosheet, confined catalytic film and preparation method thereof
CoFeCuMn LDH nanosheets were prepared by one-step hydrothermal method and a limited-domain catalytic film was constructed, which solved the problems of low PMS degradation efficiency and rate and poor performance of nanocatalytic films in the prior art, and achieved efficient and rapid degradation of new pollutants and high water flux.
Patent Information
- Application Number
- CN202510071369.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-16
AI Technical Summary
When the prior art uses the advanced oxidation process of monosulfate (PMS) to degrade new pollutants, the degradation efficiency and rate still need to be improved, and the nanocatalytic film has low permeability and poor stability, which limits its development and application.
CoFeCuMn LDH nanosheets were prepared by one-step hydrothermal method, and stacked them on the membrane surface layer by vacuum suction filtration to form a CoFeCuMn LDH confined catalytic film.
The degradation efficiency and rate of new pollutants has been significantly improved. The CoFeCuMn LDH limited-domain catalytic membrane can achieve 100% ranitidine removal rate in a very short time and maintain high water flux, overcoming the membrane permeability-selectivity trade-off effect.
Smart Images

Figure CN119490236B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment, and in particular to a CoFeCuMn LDH nanosheet, a confined catalytic membrane and a preparation method thereof. Background Art
[0002] Global urbanization and industrial development have exacerbated water shortages and have caused water bodies to be contaminated by new pollutants including pharmaceuticals, personal care products, endocrine disruptors and persistent organic pollutants, making the demand for clean water resources more urgent. New pollutants are persistent, difficult to degrade, and bioaccumulate. They are easy to migrate and transform in the environment. They have the "three-hazard" risks of mutagenicity, teratogenicity and carcinogenicity. They are believed to have ecological and physiological genetic toxicity that cannot be ignored to the environment and organisms of water bodies under relatively low concentration conditions and threaten human health. Their governance is a complex system engineering.
[0003] The advanced oxidation process (AOP) based on peroxymonosulfate (PMS) has become a promising method for rapid degradation of new pollutants under mild conditions due to its ability to produce a variety of active species (free radicals, etc.). However, the degradation efficiency and rate of new pollutants using this process still need to be improved.
[0004] In addition, the degradation of new pollutants can be improved by fixing nanocatalysts on the membrane surface to prepare nanocatalytic membranes. However, the performance of the membrane depends not only on the selectivity of the target substance, but also on the permeability; the membrane permeability-selectivity trade-off effect remains the main challenge for synthetic membranes, because the increase in permeability usually leads to the sacrifice of selectivity, and vice versa. Existing nanocatalytic membranes often have problems such as low permeability and low stability, which also limits their development and practical application.
[0005] The disclosure of the above background technology content is only used to assist in understanding the concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed on the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a CoFeCuMn LDH nanosheet, a confined catalytic membrane and a preparation method thereof, which significantly improve the degradation efficiency and rate of new pollutants.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention discloses a method for preparing CoFeCuMn LDH nanosheets, comprising the following steps:
[0009] A1: Dissolve cobalt salt, iron salt, copper salt and manganese salt in pure water according to a preset ratio to prepare a first solution, dissolve sodium hydroxide in pure water to prepare a second solution, and dissolve sodium carbonate in pure water to prepare a third solution;
[0010] A2: adding the first solution and the second solution to the third solution and stirring to obtain a mixed solution;
[0011] A3: performing a hydrothermal reaction on the mixed solution;
[0012] A4: centrifuge and wash the product obtained in step A3 to obtain a precipitate;
[0013] A5: Drying the precipitate to obtain CoFeCuMn LDH nanosheets.
[0014] Preferably, the cobalt salt in step S1 is at least one of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, cobalt acetate tetrahydrate, and cobalt chloride hexahydrate; the iron salt is at least one of ferric nitrate nonahydrate, ferric chloride trihydrate, anhydrous ferric chloride, ferric acetate tetrahydrate, and ferric sulfate pentahydrate; the copper salt is at least one of copper nitrate trihydrate, copper chloride dihydrate, copper acetate monohydrate, and copper sulfate pentahydrate; the manganese salt is at least one of manganese nitrate tetrahydrate, manganese sulfate tetrahydrate, manganese chloride tetrahydrate, manganese acetate tetrahydrate, and anhydrous manganese nitrate.
[0015] Preferably, the first solution is prepared by dissolving the cobalt salt, the iron salt, the copper salt and the manganese salt in pure water in a molar ratio of (1~2):(1~2):(1~2):(1~2).
[0016] Preferably, the concentrations of the cobalt salt, the iron salt, the copper salt, and the manganese salt in the first solution are 8 mol / L to 16 mol / L, respectively.
[0017] Preferably, the concentration of sodium hydroxide in the second solution is 0.02 g / mL to 0.04 g / mL.
[0018] Preferably, the concentration of sodium carbonate in the third solution is 0.06 g / mL to 0.1 g / mL.
[0019] Preferably, step A2 specifically comprises: adding the first solution and the second solution into the third solution and stirring at room temperature, and adjusting the pH value of the solution to 9-10 to obtain the mixed solution.
[0020] Preferably, the hydrothermal reaction conditions in step A3 are 60° C. to 130° C. and the time is 12 h to 24 h.
[0021] Preferably, step A4 specifically comprises: washing the product obtained in step A3 with pure water and ethanol at least three times under centrifugal conditions, wherein the centrifugal rate during the centrifugation process is 10000r / min~11000r / min, and the centrifugation time for one wash is 5min~10min.
[0022] Preferably, the drying temperature of the drying step in step A5 is 25° C. to 40° C., and the drying time is 24 h to 48 h.
[0023] In a second aspect, the present invention discloses a CoFeCuMn LDH nanosheet, which is prepared by the preparation method of the CoFeCuMn LDH nanosheet described in the first aspect.
[0024] In a third aspect, the present invention discloses a method for preparing a CoFeCuMn LDH confined catalytic film, comprising the following steps:
[0025] B1: Grinding the CoFeCuMn LDH nanosheets described in the second aspect, and ultrasonically dispersing them in pure water to obtain a suspension;
[0026] B2: The suspension is filtered onto a polymer base membrane and dried to obtain a CoFeCuMn LDH confined catalytic membrane.
[0027] Preferably, the power of ultrasonic dispersion in step B1 is 50W~2000W, and the time is 1h~3h.
[0028] Preferably, the mass of the ultrasonically dispersed CoFeCuMn LDH nanosheets is calculated based on the effective area of the polymer base film, and the calculation formula is: m=aS, where m represents the mass of the CoFeCuMn LDH nanosheets in mg, and S represents the effective area of the polymer base film in cm 2 , a represents the preset multiple, and the value range of a is 0.36 ~ 0.9.
[0029] Preferably, the polymer base film is one of cellulose acetate film, polyvinylidene fluoride film and polyacrylonitrile film.
[0030] Preferably, the average pore size of the polymer base membrane is less than or equal to 0.22 μm.
[0031] In a fourth aspect, the present invention discloses a CoFeCuMn LDH confined catalytic membrane, which is prepared by the preparation method of the CoFeCuMn LDH confined catalytic membrane described in the third aspect.
[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: the CoFeCuMn LDH nanosheets, confined catalytic membranes and preparation methods thereof proposed in the present invention adopt a simple and environmentally friendly one-step hydrothermal method to prepare a layered LDH catalyst comprising a quaternary metal of cobalt, iron, copper and manganese; the method of the present invention can prepare a two-dimensional sheet-shaped CoFeCuMn LDH nanosheet; experiments verify that the two-dimensional sheet-shaped CoFeCuMn LDH nanosheet has a high PMS catalytic activity, and a 100% ranitidine removal rate can be achieved in 5 minutes, and the degradation efficiency and rate of new pollutants are significantly improved; more importantly, the two-dimensional sheet-shaped CoFeCuMn LDH nanosheet also provides good conditions for subsequent stacking on the membrane surface by vacuum filtration to construct a confined space; further, the nanosheets are disorderly stacked on the polymer base membrane to produce abundant interlayer and intralayer nanochannels, forming a confined space and allowing water molecules to pass quickly, while ensuring the ultra-high water flux of the catalytic membrane, and having ultra-high PMS catalytic activity to achieve extremely fast catalytic degradation of new pollutants. Through experimental verification, it is found that the CoFeCuMn LDH nanosheets and CoFeCuMn LDH confined catalytic membranes prepared by the preparation method of the present invention have very good activation effects on PMS, and can remove 100% of ranitidine in a very short time. Among them, the CoFeCuMn LDH confined catalytic membrane that activates PMS can achieve a 100% ranitidine removal rate in the water outlet (within 1 second); and after the CoFeCuMn LDH confined catalytic membrane activates PMS, it can achieve 100% removal of various new pollutants in a very short retention time, and has good wide applicability. The CoFeCuMn LDH confined catalytic membrane successfully overcomes the membrane permeability-selectivity trade-off effect in water purification, and the first-order reaction rate constant is 7.01ms -1 , i.e. 420600min -1 , which is higher than all the current catalytic membrane research. At the same time, it can maintain a stable 100% degradation of ranitidine at a flux of about 3300LMH, providing a technical reference for the practical application of membrane confined catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a flow chart of the preparation method of CoFeCuMn LDH nanosheets disclosed in Example 1 of the present invention;
[0034] Figure 2 is a scanning electron microscope image of the CoFeCuMn LDH nanosheet of Example 2 of the present invention;
[0035] Figure 3 It is a flow chart of the preparation method of the CoFeCuMn LDH confined catalytic film disclosed in Example 3 of the present invention;
[0036] Figure 4 is a scanning electron microscope image of the surface of the CoFeCuMn LDH confined catalytic film of Example 4 of the present invention;
[0037] Figure 5 is a scanning electron microscope image of a cross section of the CoFeCuMn LDH confined catalytic membrane of Example 4 of the present invention;
[0038] Figure 6 It is a schematic diagram of the test results of the removal rate of ranitidine in two examples of the present invention and two comparative examples;
[0039] Figure 7 It is a schematic diagram of the first-order reaction rate constant results of CoFeCuMn LDH nanosheets / PMS in a heterogeneous system and the first-order reaction rate constant results of PMS alone;
[0040] Figure 8 This is a schematic diagram of the first-order reaction rate constant results of CoFeCuMn LDH confined catalytic film / PMS;
[0041] Fig. 9 This is a schematic diagram of the results of the continuous membrane catalytic experiment using CoFeCuMn LDH confined catalytic membrane / PMS to test the removal rate of ranitidine;
[0042] Fig.10 It is a schematic diagram of the effects of CoFeCuMn LDH confined catalytic membrane / PMS, CoFeCuMn LDH confined catalytic membrane alone and PMS alone on the degradation of new pollutants in water bodies. DETAILED DESCRIPTION
[0043] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0044] It should be noted that when a component is referred to as being "fixed to" or "disposed on" another component, it can be directly on the other component or indirectly on the other component. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element. In addition, connection can be used for both fixing and circuit / signal communication.
[0045] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0046] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0047] Although the advanced oxidation process (AOP) based on peroxymonosulfate (PMS) is a promising method for rapid degradation of new pollutants under mild conditions due to its ability to produce a variety of active species (free radicals, etc.), PMS-AOP also has some limitations, including low yield and ultra-short life of active species, mass transfer limitations, and agglomeration and loss of nanocatalysts. Through research, it is found that the reason is that particles, molecules and ions confined in nanoscale space will exhibit chemical and physical properties that are completely different from those in the bulk phase. The present invention constructs a nano-confined catalytic membrane by fixing two-dimensional nanosheets on the membrane surface, thereby overcoming the inherent limitations of PMS-AOP. At the nanoscale, organic pollutants and active species are enriched in the nanoscale space, effectively accelerating collision and mass transfer. At the same time, the properties of the catalytic material will also be affected by the nano-confined scale, thereby changing the catalytic activity and chemical conversion process in the system, reducing the activation energy barrier, etc.
[0048] The key advantages of using layered double hydroxides (LDHs) to assemble nanoconfined catalytic membranes are low cost, high catalytic activity, and the ability to be stacked layer by layer on the membrane surface to construct a nanoscale confined space. Among them, the LDH functional membrane has abundant interlayer and intralayer nanochannels, which can effectively promote the transport of water molecules and provide high water flux. The synthesis of two-dimensional transition metal (Co, Ni, Fe, Cu or Mn) LDHs was used for PMS-AOP. Further experimental studies have shown that cobalt-based LDHs doped with Fe, Cu or Mn elements have a good activation effect on PMS. In addition, multimetallic LDHs show better activity than single metal LDHs, which is due to changes in electronic structure or improvements in synergistic electron transfer between different metals. At the same time, multimetallic LDHs can significantly improve the intrinsic activity of a single active site. Therefore, compared with bimetallic LDHs, the preparation of multimetallic (such as quaternary) LDHs is more suitable for PMS-AOPs. Since the morphology and activity of LDH are affected by various factors, such as reaction conditions or the ratio of metal divalent and trivalent cations, the preparation of tetrametallic LDH nanosheets and the assembly of catalytic films with high PMS catalytic activity remain a challenge.
[0049] In summary, considering the defects of low permeability and low stability of nanocatalytic membranes in the existing technology, developing a quaternary layered LDH catalyst with ultra-high PMS catalytic activity and preparing it into a confined catalytic membrane is an effective strategy to break the membrane permeability-selectivity trade-off effect, thereby achieving ultra-high flux. The ultra-efficient degradation of new pollutants in water bodies makes the confined catalytic membrane have higher practical application value and provides a solution for deep water treatment.
[0050] Through research, it was found that among transition metals, Co has the highest catalytic activity for PMS, and multi-metal LDH has better catalytic activity than single metal LDH. Therefore, the present invention further uses cobalt-based multi-metal LDH to activate PMS to degrade new pollutants. In order to further explore the activity mechanism of single metal, bimetallic and multi-metallic LDH, the best performing LDH was selected, and the molecular mechanism of the interaction between Co and other transition metals to enhance the activity of LDH was explored through density functional theory (DFT) calculations. By studying the projected density of states (PDOS) of various metals, it was found that the d-band center of CoFeCuMn LDH before adsorption ( ) value is the highest (1.17eV), which indicates that the d-band center of CoFeCuMn LDH has more lone pairs of electrons, which is most conducive to PMS adsorption. Compared with other LDH materials, it is most conducive to PMS activation. Therefore, in order to achieve efficient degradation of new pollutants in water bodies, break the permeability-selectivity trade-off effect of the membrane, and make the confined catalytic membrane have greater application value and potential, the present invention prepares CoFeCuMn LDH catalyst with ultra-high PMS catalytic activity by a one-step hydrothermal method. The morphology is uniform hexagonal and the layer is thin. It is loaded on the bottom membrane through vacuum assisted filtration, so as to achieve ultra-high efficiency removal of new pollutants in water bodies by the catalytic membrane at ultra-high flux.
[0051] like Figure 1 As shown, Embodiment 1 of the present invention discloses a method for preparing CoFeCuMn LDH nanosheets, comprising the following steps:
[0052] A1: Dissolve cobalt salt, iron salt, copper salt and manganese salt in pure water according to a preset ratio to prepare a first solution, dissolve sodium hydroxide in pure water to prepare a second solution, and dissolve sodium carbonate in pure water to prepare a third solution;
[0053] Among them, the cobalt salt is at least one of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, cobalt acetate tetrahydrate, and cobalt chloride hexahydrate; the iron salt is at least one of ferric nitrate nonahydrate, ferric chloride trihydrate, anhydrous ferric chloride, ferric acetate tetrahydrate, and ferric sulfate pentahydrate; the copper salt is at least one of copper nitrate trihydrate, copper chloride dihydrate, copper acetate monohydrate, and copper sulfate pentahydrate; the manganese salt is at least one of manganese nitrate tetrahydrate, manganese sulfate tetrahydrate, manganese chloride tetrahydrate, manganese acetate tetrahydrate, and anhydrous manganese nitrate.
[0054] The first solution is prepared by dissolving cobalt salt, iron salt, copper salt and manganese salt in pure water in a molar ratio of (1~2):(1~2):(1~2):(1~2), and the molar ratio of cobalt salt, iron salt, copper salt and manganese salt is, for example, 2:2:1:2; further, the concentrations of cobalt salt, iron salt, copper salt and manganese salt in the first solution are 8 mol / L~16 mol / L, respectively, the concentration of sodium hydroxide in the second solution is 0.02 g / mL~0.04 g / mL, for example, 0.024 g / mL, and the concentration of sodium carbonate in the third solution is 0.06 g / mL~0.1 g / mL, for example, 0.0636 g / mL.
[0055] Among them, preferably, ultrapure water is used in preparing the first solution, the second solution and the third solution.
[0056] A2: adding the first solution and the second solution to the third solution and stirring to obtain a mixed solution;
[0057] Specifically, the first solution and the second solution are added to the third solution and stirred at room temperature, and the pH value of the solution is adjusted to 9-10, for example, pH 10, to obtain a mixed solution.
[0058] A3: subjecting the mixed solution to a hydrothermal reaction;
[0059] The mixed solution is poured into the inner tank of the reactor for hydrothermal reaction, and the conditions of the hydrothermal reaction are 60°C~130°C and the time is 12h~24h.
[0060] A4: centrifuge and wash the product obtained in step A3 to obtain a precipitate;
[0061] The product obtained in step A3 is washed at least three times with pure water and ethanol under centrifugal conditions, wherein the centrifugal rate during the centrifugation process is 10000 r / min to 11000 r / min, and the centrifugal time for each wash is 5 min to 10 min; for example, each wash is centrifuged for 10 min at a centrifugal rate of 10000 r / min. Ultrapure water and ethanol are preferably used in the washing process.
[0062] A5: Dry the precipitate to obtain CoFeCuMn LDH nanosheets.
[0063] The precipitate is placed in a vacuum oven and dried for a certain period of time, and the product is ground to obtain brown powder CoFeCuMnLDH nanosheets. Specifically, the drying temperature of the drying step is 25°C~40°C, and the time is 24h~48h; for example, drying at 40°C for 24h.
[0064] The second embodiment of the present invention discloses a CoFeCuMn LDH nanosheet, which is prepared by the preparation method of the CoFeCuMnLDH nanosheet in the first embodiment, such as Figure 2 Shown is a scanning electron microscope image of the CoFeCuMn LDH nanosheet of this embodiment. It can be seen from the morphology image of the CoFeCuMn LDH nanosheet that the CoFeCuMn LDH nanosheet prepared by the preparation method of the CoFeCuMnLDH nanosheet of Example 1 of the present invention is in the form of a two-dimensional sheet, which provides good conditions for the subsequent construction of a confined space by stacking layer by layer on the membrane surface through a vacuum filtration method.
[0065] like Figure 3 As shown, Embodiment 3 of the present invention discloses a method for preparing a CoFeCuMn LDH confined catalytic film, comprising the following steps:
[0066] B1: Grind the CoFeCuMn LDH nanosheets prepared in Example 2, and ultrasonically disperse them in pure water to obtain a suspension;
[0067] The power of ultrasonic dispersion is 50W~2000W, and the time is 1h~3h to obtain a uniformly dispersed suspension, wherein ultrapure water is preferably used for ultrasonic dispersion.
[0068] The mass of the ultrasonically dispersed CoFeCuMn LDH nanosheets is calculated based on the effective area of the polymer substrate, and the calculation formula is: m=aS, where m represents the mass of the CoFeCuMn LDH nanosheets in mg, and S represents the effective area of the polymer substrate in cm 2 , a represents a preset multiple, and the value range of a is 0.36 ~ 0.9, preferably, the value range of a is 0.5~0.9. For example, when a polymer base film with a diameter of 5 cm is used, the effective diameter of the polymer film is 4.2 cm, and the effective area is about 13.85 cm 2 At this time, 5 mg to 12.5 mg of CoFeCuMn LDH nanosheets need to be ultrasonically dispersed in pure water to obtain a suspension, and then step B2 is further performed.
[0069] B2: The suspension is filtered onto the polymer base membrane and dried to obtain the CoFeCuMn LDH confined catalytic membrane.
[0070] Among them, the suspension is filtered on a polymer base membrane and dried at room temperature to obtain a CoFeCuMn LDH confined catalytic membrane. The polymer base membrane is a cellulose acetate membrane, a polyvinylidene fluoride membrane, or a polyacrylonitrile membrane, and the average pore size of the polymer base membrane is less than or equal to 0.22 μm. For example, in this step, 300 mL to 500 mL of a uniformly dispersed suspension is filtered on a polymer base membrane with an average pore size of 0.22 μm, and the catalyst loading on the polymer base membrane is preferably 0.5 to 0.9 mg / cm 2 .
[0071] The fourth embodiment of the present invention discloses a CoFeCuMn LDH confined catalytic film, which is prepared by the preparation method of the CoFeCuMnLDH confined catalytic film of the third embodiment, such as Figure 4 and Figure 5 The following are scanning electron microscope images of the surface and cross section of the CoFeCuMn LDH confined catalyst membrane of this embodiment, wherein Figure 4 The morphological image of the CoFeCuMn LDH confined catalytic membrane surface shown in FIG. 1 shows that after the material is filtered into a membrane, the material evenly covers the base membrane, and there are no obvious cracks or defects on the membrane surface. Figure 5 From the morphological image of the cross-section of the CoFeCuMn LDH confined catalytic membrane shown, it can be seen that the material layer thickness is 2.65μm, and the nanosheets are stacked disorderly on the base membrane, thereby producing abundant interlayer and intralayer nanochannels, forming a confined space while also allowing water molecules to pass quickly, ensuring a high water flux of the catalytic membrane.
[0072] The CoFeCuMn LDH confined catalytic membrane can be used to degrade new pollutants. Specifically, the steps of using the CoFeCuMnLDH confined catalytic membrane to degrade new pollutants include: placing the CoFeCuMn LDH confined catalytic membrane in a suction filtration device to degrade new pollutants, the target pollutant is, for example, ranitidine, the oxidant is PMS, and the applied pressure is 0.2 bar ~ 1bar; first pass 30 mL of water to stabilize the water flux and removal effect, then select a certain time interval to sample, use a UV-visible spectrophotometer at a wavelength of 314nm to perform absorbance detection, and combine the standard working curve to calculate the residual concentration and removal rate of ranitidine in the aqueous solution. Among them, the concentration of the ranitidine aqueous solution is preferably 5mg / L; based on the standard of good degradation effect and small PMS dosage, the amount of PMS is selected as 0.108mM; the applied pressure is 0.3bar, at this time the membrane has a high flux and can degrade ranitidine 100%.
[0073] The CoFeCuMn LDH nanosheets and preparation methods thereof, and the CoFeCuMn LDH confined catalytic membranes and preparation methods thereof in the above-mentioned embodiments are further described in detail below with reference to specific embodiments.
[0074] The preparation method of the CoFeCuMn LDH nanosheets and the CoFeCuMn LDH confined catalytic film in this specific embodiment includes:
[0075] S1: dissolving cobalt nitrate hexahydrate, anhydrous manganese nitrate, ferric nitrate nonahydrate, and copper nitrate trihydrate in ultrapure water at a molar ratio of 2:2:1:2 to prepare a first solution, wherein the concentrations of cobalt nitrate hexahydrate, anhydrous manganese nitrate, and copper nitrate trihydrate in the first solution are 16 mol / L, and the concentration of ferric nitrate nonahydrate is 8 mol / L, dissolving sodium hydroxide in ultrapure water to prepare a second solution with a concentration of 0.024 g / mL, and dissolving sodium carbonate in ultrapure water to prepare a third solution with a concentration of 0.0636 g / mL;
[0076] S2: adding the first solution and the second solution to the third solution, adjusting the pH of the solution to 10, to obtain a mixed solution;
[0077] S3: Pour the mixed solution into the inner tank of the reactor for hydrothermal reaction at 60° C. for 12 hours;
[0078] S4: washing the product obtained in step S3 with ultrapure water and ethanol by centrifugation at least three times to remove impurities;
[0079] S5: The product obtained in step S4 is placed in an oven at 40° C. and dried for 24 hours to obtain dried CoFeCuMn LDH nanosheets.
[0080] S6: Grind the CoFeCuMn LDH nanosheets into powder using a mortar, disperse them in ultrapure water and ultrasonicate for 2 hours to obtain a uniformly dispersed suspension;
[0081] S7: Prepare cellulose acetate (MCE) polymer membrane and use a vacuum filtration device to load the suspension in step S6 onto the MCE bottom membrane. The loading amount is 0.9 mg / cm 2 , and then dried in an oven at 40°C to obtain a CoFeCuMn LDH confined catalytic film.
[0082] The removal effect of the CoFeCuMn LDH nanosheets obtained in the above step S5 and the CoFeCuMnLDH confined catalytic film obtained in the above step S7 on new pollutants is further described in detail below.
[0083] CoFeCuMn LDH nanosheets / PMS and CoFeCuMn LDH confined catalytic membrane / PMS were used as two groups of examples to remove new pollutants: the CoFeCuMn LDH nanosheets obtained in step S5 were placed in a beaker (traditional heterogeneous system), and the CoFeCuMn LDH confined catalytic membrane obtained in step S7 was placed in a filtration device to degrade new pollutants. The target pollutant was ranitidine with a concentration of 5 mg / L, and the oxidant was PMS. The amount of PMS was 0.108 mM. The mass of CoFeCuMn LDH in the traditional heterogeneous system and the membrane system was the same, and the external pressure of the filtration device was 0.3 bar. First, 30 mL of water was passed to stabilize the water flux and removal effect, and then samples were taken at certain time intervals. The absorbance was detected at a wavelength of 314 nm using a UV-visible spectrophotometer, and the residual concentration and removal rate of ranitidine in the aqueous solution were calculated in combination with the standard working curve.
[0084] In addition, two groups of comparative examples were added. In one group of comparative examples, the CoFeCuMn LDH confined catalytic membrane obtained in step S7 was placed in a filtration device using the above steps to degrade new pollutants, but the oxidant PMS was not added, to test its removal effect on ranitidine; in the other group of comparative examples, only the oxidant PMS was used in the above steps, without adding catalysts such as CoFeCuMnLDH nanosheets or CoFeCuMn LDH confined catalytic membranes, to test its removal effect on ranitidine.
[0085] The test results of the above examples and comparative examples for the removal rate of ranitidine are as follows Figure 6As shown in the figure, it can be seen that in the stable catalytic process, the CoFeCuMn LDH confined catalytic membrane with activated PMS can achieve a 100% ranitidine removal rate in the water outlet (within 1 second), and the heterogeneous system of the CoFeCuMn LDH nanosheets with activated PMS achieves a 100% ranitidine removal rate in 5 minutes, wherein the CoFeCuMn LDH confined catalytic membrane has a ranitidine removal rate of almost 0 without the addition of the oxidant PMS, proving that the adsorption effect of the membrane is negligible, and the self-degradation in the case of only using the oxidant PMS is about 20% in 30 minutes, proving that the system achieves rapid degradation of new pollutants under catalytic oxidation. Therefore, it can be seen that the CoFeCuMn LDH nanosheets obtained in step S5 and the CoFeCuMn LDH confined catalytic membrane obtained in step S7 have very good activation effects on PMS, and the confined catalytic membrane exhibits a faster degradation effect than the heterogeneous system.
[0086] The following further calculations of the first-order rate constants for the heterogeneous system and the confined catalytic membrane system are compared as follows: Figure 7 and Figure 8 As shown, Figure 7 The figure in the figure shows the first-order reaction rate constant results of CoFeCuMn LDH nanosheets / PMS in a heterogeneous system and the first-order reaction rate constant results of PMS alone. Figure 8 The first-order reaction rate constant (k value) of CoFeCuMn LDH confined catalyst membrane / PMS is shown in Figure 1, where the amount of CoFeCuMn LDH in the nanosheet and confined catalyst membrane systems is the same. Figure 7 As shown in Figure 2, the first-order reaction rate constant of CoFeCuMn nanosheets / PMS (0.63247 min -1 ) is much larger than the first-order reaction rate constant of PMS (0.00756min -1 ), indicating that CoFeCuMn nanosheets have a good PMS activation effect and greatly enhance the degradation rate of ranitidine. Figure 8 It can be seen that the CoFeCuMn LDH confined catalytic film can achieve 100% degradation of ranitidine within 1.01ms, and the first-order reaction rate constant of the CoFeCuMn LDH confined catalytic film (7.01ms -1 That is 420600min -1 ) is a heterogeneous system (0.63247min -1 ) of 6.65×10 5 times, showing that the confinement effect greatly enhances the degradation efficiency of new pollutants, indicating that the confined catalytic membrane has greater application advantages. Figure 8 The calculation formula of retention time is: m =(Vm ×M m ) / (J×S), where r m 、V m 、M m , J, and S are retention time (ms), pore volume (cm 3 / g), total membrane mass (g), water flux (LMH), membrane effective filtration area (m 2 ).
[0087] In order to evaluate the stability of CoFeCuMn LDH confined catalytic membrane / PMS, a continuous membrane catalytic experiment was further conducted. The test conditions in this process were the same as the above steps of using CoFeCuMn LDH confined catalytic membrane / PMS to test the removal rate of ranitidine. The test results are shown in Fig. 9 As shown, from Fig. 9 It can be seen that the CoFeCuMn LDH confined catalytic film can stably process 2.18×10 5 The ranitidine aqueous solution of BV has a flux of about 3300LMH and a retention time of about 1.01ms. During this period, the ranitidine removal rate remained at 100%, successfully overcoming the trade-off effect of membrane permeability-selectivity in water purification; where BV represents the bed volume, that is, the number of times the aqueous solution is treated by the membrane material layer; the calculation formula is: BV=volume of solution passing through the membrane / (mass of the material layer*pore volume of the material layer), where the unit of the volume of solution passing through the membrane is mL, the unit of the mass of the material layer is g, and the unit of the pore volume of the material layer is cm 3 / g.
[0088] The degradation effects of CoFeCuMn LDH confined catalytic membrane / PMS on drugs (ofloxacin, oxytetracycline), endocrine disruptors (bisphenol A), and dyes (methyl orange, rhodamine B, methylene blue) were further tested, and the degradation effects of CoFeCuMnLDH confined catalytic membrane alone and PMS alone on these new pollutants in water bodies were used as two comparative groups. The test results are as follows Fig.10 As shown, from Fig.10 It can be seen that the CoFeCuMn LDH confined catalytic membrane / PMS can achieve 100% degradation of oxytetracycline, bisphenol A, methyl orange, rhodamine B, and methylene blue at a flux of about 3300LMH, and the removal rate of ofloxacin can reach 99%, confirming the ultrafast degradation rate of CoFeCuMn LDH confined catalytic membrane / PMS and its wide applicability; while the degradation effects of the single CoFeCuMn LDH confined catalytic membrane and the single PMS on each new pollutant are poor.
[0089] In summary, the CoFeCuMn LDH nanosheets and CoFeCuMn LDH confined catalytic films prepared in the embodiments of the present invention have the following significant advantages compared with the prior art:
[0090] (1) The material described in the present invention is cheap and readily available, has low cost, does not involve the use of toxic solvents, has a low synthesis temperature, is environmentally friendly, can be prepared by a one-step hydrothermal method, has a simple method, and has the potential for large-scale preparation.
[0091] (2) The present invention couples the advanced oxidation process with membrane filtration to achieve complete removal of new pollutants through mineralization and direct oxidation, thus avoiding the problem of re-disposal of new pollutant concentrates.
[0092] (3) The confined catalytic membrane of the present invention has an ultra-fast reaction rate and can achieve 100% degradation of a variety of new pollutants including ranitidine within 1.01 ms, with a first-order rate constant of 7.01 ms. -1 , i.e. 420600min -1 , higher than all current catalytic membrane research.
[0093] (4) The confined catalytic membrane of the present invention has an ultra-high water flux of about 3300 L·m -2 h -1 (LMH), this water flux is at the most advanced level in the membrane field, and a variety of new pollutants can be removed at a 100% rate at this water flux, and 2.18×10 5 Aqueous solution of ranitidine from BV.
[0094] (5) The confined catalytic membrane of the present invention breaks the trade-off effect between membrane permeability and selectivity, making the confined catalytic membrane valuable and potential for practical applications.
[0095] The background section of the present invention may contain background information about the problem or environment of the present invention, rather than describing the prior art by others. Therefore, the content contained in the background section is not an admission by the applicant that the prior art is available.
[0096] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, in the absence of mutual contradiction, the technical personnel in this field can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope defined by the attached claims.
Claims
1. A method for preparing CoFeCuMn LDH nanosheets, characterized in that: The following steps are involved: A1: dissolving a cobalt salt, an iron salt, a copper salt and a manganese salt in pure water in a preset ratio to prepare a first solution, dissolving sodium hydroxide in pure water to prepare a second solution, and dissolving sodium carbonate in pure water to prepare a third solution, wherein the first solution is prepared by dissolving the cobalt salt, the iron salt, the copper salt and the manganese salt in pure water in a molar ratio of (1-2):(1-2):(1-2):(1-2); A2: adding the first solution and the second solution to the third solution and stirring at room temperature, adjusting the pH value of the solution to 9-10 to obtain a mixed solution; A3: performing a hydrothermal reaction on the mixed solution, wherein the hydrothermal reaction condition is 60° C. to 130° C. and the time is 12 h to 24 h; A4: centrifuge and wash the product obtained in step A3 to obtain a precipitate; A5: Drying the precipitate to obtain CoFeCuMn LDH nanosheets.
2. The method for preparing CoFeCuMn LDH nanosheets according to claim 1, characterized in that: The cobalt salt in step S1 is at least one of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, cobalt acetate tetrahydrate, and cobalt chloride hexahydrate; the iron salt is at least one of ferric nitrate nonahydrate, ferric chloride trihydrate, anhydrous ferric chloride, ferric acetate tetrahydrate, and ferric sulfate pentahydrate; the copper salt is at least one of copper nitrate trihydrate, copper chloride dihydrate, copper acetate monohydrate, and copper sulfate pentahydrate; the manganese salt is at least one of manganese nitrate tetrahydrate, manganese sulfate tetrahydrate, manganese chloride tetrahydrate, manganese acetate tetrahydrate, and anhydrous manganese nitrate.
3. The method for preparing CoFeCuMn LDH nanosheets according to claim 1, characterized in that: The concentrations of the cobalt salt, the iron salt, the copper salt, and the manganese salt in the first solution are 8 mol / L to 16 mol / L, respectively; the concentration of sodium hydroxide in the second solution is 0.02 g / mL to 0.04 g / mL; and the concentration of sodium carbonate in the third solution is 0.06 g / mL to 0.1 g / mL.
4. The method for preparing CoFeCuMn LDH nanosheets according to claim 1, characterized in that: Step A4 specifically includes: washing the product obtained in step A3 with pure water and ethanol at least three times under centrifugal conditions, wherein the centrifugal rate during the centrifugation process is 10000r / min~11000r / min, and the centrifugation time for one wash is 5min~10min; the drying temperature of the drying step in step A5 is 25℃~40℃, and the time is 24h~48h.
5. A CoFeCuMn LDH nanosheet, characterized in that: The CoFeCuMnLDH nanosheets are prepared by the preparation method of any one of claims 1 to 4.
6. A method for preparing a CoFeCuMn LDH confined catalytic film, characterized in that: The following steps are involved: B1: grinding the CoFeCuMn LDH nanosheets according to claim 5, and ultrasonically dispersing them in pure water to obtain a suspension; B2: The suspension is filtered onto a polymer base membrane and dried to obtain a CoFeCuMn LDH confined catalytic membrane.
7. The method for preparing the CoFeCuMn LDH confined catalytic film according to claim 6, characterized in that: The power of ultrasonic dispersion in step B1 is 50W~2000W, the time is 1h~3h, and the mass of the ultrasonically dispersed CoFeCuMn LDH nanosheets is calculated according to the effective area of the polymer base film, and the calculation formula is: m=aS, m represents the mass of the CoFeCuMn LDH nanosheets, the unit is mg, S represents the effective area of the polymer base film, the unit is cm 2 , a represents the preset multiple, and the value range of a is 0.36 ~ 0.
9.
8. The method for preparing the CoFeCuMn LDH confined catalytic film according to claim 6, characterized in that: The polymer base membrane is one of cellulose acetate membrane, polyvinylidene fluoride membrane and polyacrylonitrile membrane, and the average pore size of the polymer base membrane is less than or equal to 0.22 μm.
9. A CoFeCuMn LDH confined catalytic film, characterized in that: The film is prepared by the method for preparing the CoFeCuMn LDH confined catalytic film according to any one of claims 6 to 8.